2013
DOI: 10.1024/0939-5911.a000257
|View full text |Cite
|
Sign up to set email alerts
|

Indikatoren für das Ausmaß jugendlichen Rauschtrinkens in Bayern

Abstract: Fragestellung: Ist der Anstieg der Krankenhausbehandlungen Jugendlicher wegen einer Alkoholintoxikation ein Indikator für eine Zunahme riskanten Trinkverhaltens? Methodik: Durchgeführt wurden zwei Sekundäranalysen (Untersuchung der Straftaten und Unfälle unter Alkoholeinfluss von 10 – 20-jährigen Jugendlichen sowie der Blutalkoholkonzentrationen (BAK) von stationär behandelten Jugendlichen, n = 1 020) und eine Feldstudie (Bevölkerungsbefragung, n = 285). Ergebnisse: Die Zahl der Krankenhausbehandlungen korreli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The more than twofold increase in the treatment of acute intoxications at hospitals over the last 10 years could be explained neither by a dramatic increase in youths' consumption nor by the major shift in coding from T51 to F10.0. Changes in drinking context of adolescents and rising awareness of others directly or indirectly involved in the incident seem more plausible in explaining the trend [37,38]. …”
Section: Discussionmentioning
confidence: 99%
“…The more than twofold increase in the treatment of acute intoxications at hospitals over the last 10 years could be explained neither by a dramatic increase in youths' consumption nor by the major shift in coding from T51 to F10.0. Changes in drinking context of adolescents and rising awareness of others directly or indirectly involved in the incident seem more plausible in explaining the trend [37,38]. …”
Section: Discussionmentioning
confidence: 99%
“…Recent research has found that (a) an emergency department (ED) admission due to an AAI is not unconditionally implying frequent excessive drinking (Kraus et al, 2012) and (b) higher public awareness of risks associated with underage drinking is associated with higher numbers of ED admissions (Wurdak et al, 2013). However, little is known about habitual drinking of adolescent AAI patients and characteristics of potential subgroups.…”
Section: Introductionmentioning
confidence: 98%
“…It cannot be ruled out either that changed coding habits of medical practitioners have contributed to the increase in the number of cases in recent years. Moreover, experts assume that part of the increase may be attributable to an increased perception of excessive alcohol abuse in public places and to an elevated readiness amongst the population to make emergency calls [ 16-18 ].…”
Section: Classification Of Findingsmentioning
confidence: 99%